Etiopathogenesis of pathological mandibular fracture: literature review and case reports - Kelly Bienk DIAS; Anne Carolina Ferreira VITANCORT; Plínio Abel Alexandre da COSTA; Caroline HARTEL; Thaís Becker de Almeida SARAIVA; Sérgio Antônio SCHIEFFERDECKER (Faculdade São Leopoldo Mandic, 2023)
ABSTRACT Pathological mandibular fractures are fractures induced by pathologies affecting the mandible's base or those resulting from forces that would typically be tolerable if the bone were not compromised by an underlying condition. These fractures often present complex clinical scenarios owing to the compromised bone integrity caused by the pathology, which impedes resolution. Systemic changes may also diminish the capacity for bone neoformation, significantly limiting therapeutic options. Therefore, this study aimed to provide a comprehensive review of the published scientific literature and present clinical cases related to the treatment and prevention of pathological mandibular fractures. A literature review was conducted, focusing on case reports indexed in the MEDLINE and SCIELO databases using specific keywords as descriptors. The search yielded ten articles, which described the etiopathogenesis, classified as infectious, idiopathic, benign pathology, malignant pathology, and iatrogenic. The literature suggests that prioritizing surgery to address the underlying local pathology is crucial. Managing the remaining bone defect optimally may necessitate multiple surgical interventions. Furthermore, preventive measures should be implemented in potential iatrogenic cases. Notably, fractures of malignant, idiopathic, hereditary, and metabolic etiologies may indicate the initial manifestation of diseases.